Decision Support System for Determining Homeroom Teachers in Musda Perbaungan Private Vocational Schools Using the Simple Additive Weighting Method - Ravyson Purba (International Journal of Basic and Applied Science, 2019)
This research is based on observations, the MUSDA Perbaungan Private Vocational School is one of the vocational schools that cannot be separated from the struggle of the Regional Government of Serdang Bedagai Regency which is located in Tualang. MUSDA Perbaungan Private Vocational School has majors in Computer Network Engineering, Software Engineering, Light Vehicle Engineering, Motorcycle Engineering, and Mechanical Engineering with a total number of 45 teachers. Making a decision support system for determining homeroom teachers is very much needed by the MUSDA Perbaungan Private Vocational School. This system will make it easier to determine homeroom teachers, and also this system can help evaluate teacher performance systems that are lacking in performance standards in general. Thus, a decision support system using the Simple Additive Weighting (SAW) method is suitable to be developed in this system. This system will make it easier to find and determine teachers who are worthy of being homeroom teachers and will speed up the calculation of assessments and attributes to determine teachers who are worthy of being homeroom teachers. The Simple Additive Weighting method can be used as a method in making applications in decision making. Simple Additive Weighting uses a value ordering system in determining attribute ratings, where the rating of each attribute is summed with the weight of the attribute in question. The Simple Additive Weighting method is often also known as the weighted addition method. The basic concept of the Simple Additive Weighting method is to find the weighted sum of the performance ratings for each alternative on all attributes.